Методи просування групи у соціальній мережі Facebook - Горматій, Євгенія; Сєров, Юрій (Видавництво Львівської політехніки, 2016)
Website promotion is the continuing process used by webmasters to increase website’s views amount and bring more visitors. Many techniques such as web content development, search engine optimization, search engine submission, and viral marketing are used to increase site's traffic. With a growing popularity of social sharing many webmasters have moved to platforms like Facebook, Twitter and Instagram to increase website’s views amount.
Keywords: розкрутка; соціальні мережі; інформація; соціальне просування